Engaging siblingships. (November 2015) - Gulløv, Eva; Palludan, Charlotte; Winther, Ida Wentzel
Inspired by sociological and anthropological family studies, our point of departure is that there is neither a given nor an unequivocal prototype of sibling relationships. On the basis of qualitative interviews, dialogues and filmed observations of everyday life, we investigate how children and young people in contemporary Denmark engage emotionally in sibling relationships. It emerges that siblingships inevitably involve frictions in various forms. In the article, we analyse the impact frictions have on social relations and discuss how such dynamics in sibling relationships both reflect and influence family constitutions and dynamics.